“Los ángeles se regocijan”: Music in the Marian painting of Blasco de Grañén (1422-1459). - Zavala Arnal, Carmen M. (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
Blasco de Grañén, one of the main exponents of Aragonese Gothic painting of the second third of the 15th century, was the author of the paintings of several altarpieces made for the three Aragonese provinces, on which scenes of the Virgin and Child and the Coronation of the Virgin were represented with angels musicians. This article, as well as summarizing these iconographic subjects and types, makes a brief historic-artistic outline of each painting, describes the musical scenes and identifies their elements. Finally, some conclusions are drawn about the musical content of the paintings by Blasco de Grañén, which are characterized by their rich musical iconography.